Optimizing the thiosulfate-mediated zerovalent iron/persulfate activation systems: trade-off between Fe(III)/Fe(II) cycling and quenching effects in environmental remediation - Wang, Maolin (2025)
The remediation of organic-contaminated water is a critical environmental challenge, and iron-based persulfate (PS) activation processes have emerged as a promising solution. However, the introduction of reductive sulfur species, while accelerating the Fe(III)/Fe(II) redox cycle, may also quench reactive species, potentially compromising the efficiency of Fenton-like systems. Here we systematically investigate the trade-off between accelerated Fe(III)/Fe(II) cycling and quenching effects in the zerovalent iron/PS (ZVI/PS) system using thiosulfate (TSF) as an activator. Our results show that low-level TSF (0.03-1.00 mmol/L) effectively facilitated the removal of naphthalene (Nap) and atrazine (ATZ), respectively. This enhancement is attributed to accelerated ZVI dissolution and FeSx formation, which promote the Fe(III)/Fe(II) cycle, with Fe(IV) was identified as the primary active species. However, high-level TSF (>1.0 mmol/L) drastically reduced Nap removal due to PS consumption and active species elimination. The optimal TSF dosage of 0.20 mmol/L (TSF/PS molar ratio of 1:10) demonstrated robust organic pollutant degradation, achieving a 22-fold increase in the rate constant (kobs) for Nap removal and 0.47-7.5-fold increases for ATZ removal. These findings highlight the potential of the TSF-ZVI/PS system as a versatile and efficient solution for degrading a wide range of organic pollutants, including PAHs and herbicides, in water treatment applications.